Does raising awareness in families reduce environmental tobacco smoke exposure in wheezy children? - Nacaroglu, Hikmet Tekin; Can, Demet; Gunay, Ilker; Karkıner, Canan Sule Unsal; Gunay, Turkan; Cimrin, Dilek; Nalcabasmaz, Tugba (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Environmental tobacco smoke (ETS) is thought to increase the severity and number of attacks in wheezy children. Objective assessments are needed to change the behavior of families to reduce the exposure of wheezy children to ETS. Aim: To determine whether informing families about their children’s urinary cotinine levels curtailed the exposure of children to ETS. Material and methods: A survey was used to determine the ETS exposure level, and the urinary cotinine level of each patient was tested. Children with positive urinary cotinine levels were included in the second part of the study. The families were randomly divided into two groups: an intervention group that was advised about urinary cotinine levels by telephone and a non-intervention group that was not so advised. The groups were followed-up 2 months later, and urinary cotinine levels were measured once again. Results: The intervention group contained 65 children of average age of 24.4 ±8.9 months, of whom 46 (70.8%) were male. The non-intervention group contained 69 children of average age of 25.3 ±9.8 months (p > 0.05), of whom 52 (75.4%) were male. The urinary cotinine levels at the time of the second interview were lower in both groups. The number of cigarettes that fathers smoked at home decreased in the intervention group (p = 0.037). Conclusions: Presenting objective evidence on ETS exposure to families draws attention to their smoking habits. Measurement of cotinine levels is cheap, practical, and noninvasive. Combined with education, creating awareness by measuring cotinine levels may be beneficial.